Drones and the ethics of targeted killing - Himes, Kenneth R. 1950- (Rowman & Littlefield Publishers, 2016)
Drones have become an essential part of U.S. national security strategy, but most Americans know little about how they are used, and we receive conflicting reports about their outcomes. In Drones and the Ethics of Targeted Killing, ethicist Kenneth R. Himes provides not only an overview of the role of drones in national security but also an exploration of the ethical implications of drone warfare from the impact on terrorist organizations and civilians to how piloting drones shapes soldiers. Targeted killings have played a role in politics from ancient times through today, so the ethical challenges around how to protect against threats are not new. Himes leads readers through the ethics of targeted killings in history from ancient times to the contemporary Israeli-Palestinian conflict, then looks specifically at the new issues raised through the use of drones.